Analysis of the Effect of Hypertension Prevention Program on Hypertension Status Among Workers in Manufacturing Companies in Semarang - Hanifah Septiasary; Hanifa Maher Denny; Yuliani Setyaningsih (Journal of Social Research, 2025)
Hypertension is a leading non-communicable disease-causing mortality and reducing employee productivity. Its high prevalence in the workplace is linked to lifestyle factors and low awareness of prevention. This study aimed to analyze the effect of hypertension prevention programs on employee awareness and hypertension status in animal feed companies in Semarang. A quasi-experimental design with pre-test and post-test control groups was employed. From a population of 257 employees, 30 samples were selected for each group. Data were collected via questionnaires and observation sheets. The intervention consisted of a hypertension prevention program including sosialisasi (socialization) about hypertension prevention and routine blood pressure monitoring. Data analysis used paired t-tests and Wilcoxon tests. Sixty subjects participated, with mean ages of 43.87 years (intervention) and 40.23 years (control). In the intervention group, 60% had a family history of hypertension. Significant improvement in awareness was observed in the intervention group (p = 0.000) but not in the control group (p = 0.493). The intervention significantly reduced systolic (p = 0.000) and diastolic (p = 0.012) blood pressure and lowered hypertension prevalence from 63.3% to 40%, whereas the control group showed no change. In conclusion, workplace hypertension prevention programs effectively increase employee awareness and reduce blood pressure and hypertension prevalence. These programs are recommended as preventive strategies in occupational health management.